2004
DOI: 10.1029/2004gl019899
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric electron concentration imaging using GPS over the USA during the storm of July 2000

Abstract: A new technique for ionospheric imaging is demonstrated during a severe geomagnetic storm of 15th July 2000. The three‐dimensional time‐dependent imaging algorithm is applied to multi‐directional ground‐based GPS data and yields spatial maps of electron concentration. This technique is demonstrated by showing a series of images of the mid‐latitude ionosphere over the USA during the storm of July 2000. A strong uplift in the height of the F‐layer is observed after 20 UT on 15th July, followed by a severe latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 7 publications
2
59
0
Order By: Relevance
“…Kelley et al 2004;Heelis and Coley 2007). Yin et al (2004) showed that SAPS created a SED over the USA during the 15 July 2000 storm, influencing Global Positioning System (GPS) communications. In fact, total electron content (TEC) maps created from GPS signal processing has been extensively used to quantify the timing and intensity of SEDs (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 99%
“…Kelley et al 2004;Heelis and Coley 2007). Yin et al (2004) showed that SAPS created a SED over the USA during the 15 July 2000 storm, influencing Global Positioning System (GPS) communications. In fact, total electron content (TEC) maps created from GPS signal processing has been extensively used to quantify the timing and intensity of SEDs (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 99%
“…In addition, global dualfrequency GPS measurements provided by the International GNSS Service (IGS) are used together with a 4-D tomographic algorithm (Multi-Instrumental Data Analysis System -MIDAS) to investigate the source of the high-density plasma observed by the two EISCAT radars. This technique has been used extensively to study three major storms (Yin et al, 2006) and verified over the mainland USA using the Millstone Hill ISR (Incoherent Scatter Radar) data for the July 2000 storm (Yin et al, 2004). We will demonstrate that, when the optical and radar results are combined with global GPS data, the generation and transport of these ionospheric structures can be accurately traced and reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies of geomagnetic storms have been carried out in the US and Europe (e.g. Foster et al 2004;Yin et al 2004;Goncharenko et al 2007), investigations on ionospheric behaviour to storms in Asia are relatively few due to a lack of dense sets of GPS observations, etc. In this paper, the responses of the GPS-derived NmF2 and hmF2 to the super geomagnetic storm (20 November 2003) over South Korea using data from the dense Korean GPS Network are described.…”
Section: F-2 Layer Ionospheric Response To Stormmentioning
confidence: 99%
“…Therefore, GPS has been widely used to monitor the ionosphere (e.g. Jin et al 2004Jin et al -2007Yin et al, 2004). As the F2-layer peak electron density value (denoted as NmF2, proportional to the square of the F2 layer critical frequency foF2) is of great influence on the shape of the ionospheric electron density profile Ne(h), and also probably related to various physical processes of ionospheric activities as well as the F2-layer peak height (hmF2), the NmF2 and hmF2 are essential parameters for monitoring ionospheric activities and understanding the nature of the ionosphere.…”
Section: F-2 Layer Ionospheric Response To Stormmentioning
confidence: 99%